Aspirin for primary prevention of stroke in individuals without cardiovascular disease—A meta-analysis. Issue 1 (January 2020) - Judge, Conor; Ruttledge, Sarah; Murphy, Robert; Loughlin, Elaine; Gorey, Sarah; Costello, Maria; Nolan, Aoife; Ferguson, John; Halloran, Martin O; O'Canavan, Michelle; O'Donnell, Martin J
Background: The benefits of aspirin for primary prevention of stroke are uncertain. Methods: We performed a cumulative meta-analysis of trials investigating aspirin for primary prevention of cardiovascular disease with a focus on stroke. We assessed the effects of aspirin on non-fatal stroke, hemorrhagic stroke, non-fatal myocardial infarction, all-cause mortality, cardiovascular mortality, major gastrointestinal bleeding, and an analysis of net clinical effect, in populations without a history of clinical or subclinical cardiovascular disease. Summary of review results: Among 11 trials (157, 054 participants), aspirin was not associated with a statistically significant reduction in non-fatal stroke (odds ratio, 0.94; 95% CI, 0.85 to 1.04) but was associated with an increased risk of hemorrhagic stroke (odds ratio, 1.29; 95% CI, 1.06 to 1.56). Aspirin was not associated with a statistically significant reduction in all-cause mortality (odds ratio, 0.97; 95% CI, 0.92 to 1.03) or cardiovascular mortality (odds ratio, 0.94; 95% CI, 0.85 to 1.03). Aspirin was associated with a reduction in non-fatal myocardial infarction (odds ratio, 0.80; 95% CI, 0.69 to 0.94) and an increased risk of major gastrointestinal bleeding (odds ratio, 1.83; 95% CI, 1.43 to 2.35). Using equal weighting for non-fatal events and major bleeding, we observed no net clinical benefit with aspirin use for primary prevention. Conclusion: Our meta-analysis reports no benefit of aspirin for primary stroke prevention.